PENGGUNAAN TERAPI NON INVASIF GAMMA KNIFE DALAM PENANANGANAN TUMOR OTAK: LITERATURE REVIEW - Harahap, Iqbal Alaudilah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2024)
Background: Gamma knife radiosurgery (GKRS) is a method of stereotactic radiosurgery (SRS) therapy that used in medical therapy for benign or malignancy brain tumor patient. The aim of this article is to know efectivity of GKRS method for brain tumor therapy based on new study that focused on therapeutic advantages, type of tumor, factors that influence therapy, side effect of therapy, complication, and new study of GKRS therapy. Methods: This study is a narative literature review that be formed based on PRISMA-P guideline in 2015 through stages collecting, analysis, and citation of related journal. Colleted journal article was founded from PubMed with the topics are gamma knife, treatment, and brain tumor that include with the topics based on publication year, language, title, and abstract. Discussion: Based on the results of the analysis, GKRS is SRS therapy that common used for patient with primary brain tumor or brain metastasis. GKRS therapy for patient with brain metastasis can decrease the risk of radionecrosis (RN) than whole brain radiotherapy (WBRT). The use of GKRS most often causes several symptoms after actions such as perilesional oedema, syncope, and anxiety. New study showed there are therapy combination between SRS and WBRT such as intensity-modulated radiation therapy (IMRT) that increasead efectivity of therapy for patient with brain tumor. Conclusion: GKRS therapy showed that overall this therapy is effectiveness and recommended as non-invasive therapy for patient with primary brain tumor or brain metastasis. Keywords: Gamma Knife, Therapy, Non-Invasive, Tumor, Brain